Semantic Analysis of the Meaning of Al-‘Ilmu in the Qur'an from Toshihiko Izutsu's Perspective - Ikrom Nurdin Jamil; Ainur Rhain (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the meaning of the concept of al-‘ilmu in the Qur'an using Toshihiko Izutsu's semantic approach. The research focuses on three main dimensions: the basic meaning, relational meaning, and historical meaning of the term al-‘ilmu. The research method used is a qualitative descriptive analysis with syntagmatic and paradigmatic approaches. The research data were obtained from Qur'anic verses containing the term al-‘ilmu as well as classical references such as Mufradat Alfadz al-Qur'an by Raghib al-Asfahani and Lisan al-Arab by Ibn Manzur. The results show that al-‘ilmu has a basic meaning of knowledge and awareness. Relationally, al-‘ilmu is often associated with concepts such as hikmah (wisdom), huda (guidance), and taqwa (piety). Historically, the meaning of al-‘ilmu evolved from general knowledge in pre-Qur'anic societies to a concept encompassing theological, epistemological, and ethical perspectives in Islam. These findings contribute significantly to the study of Qur'anic semantics and the understanding of Islamic epistemology.